Production and characterization of Thermoascus aurantiacus SL16W XYLANASE - Niwat Chawachart (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Xylanase production of thermophilic fungus Thermoascus aurantiacus SL16W was studied to optimize the maximum enzyme production in solid substrate medium. Main carbon source, organic nitrogen source and inorganic nitrogen source were screened to find out each source affected to maximum xylanase production. Corncob, soybean meal and ammonium dihydrogen phosphate were selected to study the most suitable composition for xylanase production using central composite design (CCD). Maximum xylanase produced by T. aurantiacus SL16W was 5,287 U/g substrate using 1.27 g corncob, 1.32 g soybean meal and 0.04 g of NH4H2PO4 after 10 day of cultivation at 45 °C while the predicted value from response surface equation was 5,112 U/g substrate. Difference carbon sources were varied in liquid medium experiment to find out effects of xylanase induction using Glucose, lactose, D-arabinose, L-arabinose, D-psicose, D-ribose and D-xylose were tested as additional carbon sources by addition into the medium 0.05% (w/v). L-arabinose was gave the most highest xylanase activity in liquid culture. T. auantiacus SL16W was produced xylanase 6,377 U/g substate when 2.5% (w/w) of L-arabinose was added in solid medium. Xylanase from solid substrate cultivation of T. aurantiacus SL16W was purified by ammonium sulphate precipitation, DEAE-Sephadex A-50 ion-exchange chromatography, Sephacyl S-100 HR gel filtration and Hi Trap Q XL ion exchange chromatography, respectively. The enzyme was purified 9.14 folds with the specific activity of 1,384 U/mg protein. Thermoascus aurantiacus SL16W xylanase was monomeric protein with molecular weight of 33 kDa by SDS-PAGE The optimum pH and temperature were 5.0 and 75 °C, respectively. The purified xylanase was stable at pH 6.0 and temperature range 75 °C for at least 1 h incubation. The Km and Vmax value were 1.1% (w/v) and 0.793 μmole/min, respectively. at 1 mM concentration of HgSO4 and KMnO4 strongly inhibit xylanase activity, while CaCl2, KCl and NaCl were tended to increase enzyme activity. Amino acid sequences of T. aurantiacus SL16W xylanase was analyzed and showed 303 amino acids. 3D protein structure of T. aurantiacus SL16W xylanase was constructed by computer modeling method and contained 2 loops, 8 alpha helixes and 2 beta pleats. Disulphite bond was detected 1 bridge at position 255 and 261.